Shari’ah compliant healthcare centre - Jasmani, Ismail; Abdul Rahman, Julaila; Zakaria, Mohd Izzat Amir (Kulliyah of Architecture & Environmental Design, International Islamic University Malaysia, 2019)
Designing a building based on Shari’ah compliant practice is encouraged in Islamic Community. Hospitals are where people who get medicine or proper treatments sick. This institution or health care service where dealing with inpatient, outpatient and emergency cases. In Malaysia Department of Standard has been appointed Standard and Industrial Research Institute of Malaysia (SIRIM) as one body to develop, distribute, evaluate and certify standard in Malaysia. Under General Shari’ah based Quality Management System (MS 1900:2014). MS 1900: 2014 documents are specifically provide general guideline toward implementing a shari’ah management system.A Shari’ah compliant hospital is where the healthcare services rendered in the hospital are in accordance with the Islamic Teaching principle. The awareness for the need to practice Shari’ah Compliant in all aspect in Islam practicesare importance now day, where the beauty of Islam way of life and everyone can practice without bias to one races and community in all aspect in way of life in the world.